Edukasi Pemanfaatan Minyak Jelantah Dan Daun Kelor Menjadi Sabun Batang Sebagai Upaya Pencegahan Paparan Logam Berat Dari Pewarna Sintetis Dan Pestisida di Desa Tlingsing, Cawas, Klaten - Noviana Dewi; Indah Tri Susilowati; Evelyne Heny Lukitasar; Ahmad Khoirul Anwar; Daffina Ramadhani Putri Aribowo; Nastiti Sekar Indrastuti; Nova Erlyta Puspitaningrum; Layla Nur Hidayah; Devina Marva Aristawati; Satriyo Adhe; Saputra, Andi Prasetyo (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
Oxidative stress induced in cells by the generation of reactive oxygen species (ROS) is a toxic effect of heavy metals that exceed the threshold if they enter the body and can cause health threats. Apart from heavy metals that can cause oxidative stress are pesticides. The impact of oxidative stress will disrupt health because it has damaging properties on proteins, DNA and lipids. Exposure to heavy metals by workers and pesticides by farmers through skin contact, inhalation or respiration, to reduce the impact of inhalation or contact on the skin, in this service workers and farmers are given PHBS education, and one of them is by maintaining cleanliness after contact with colors or pesticides by means of wash your hands using soap. Community service is provided through counseling methods, health checks in the form of MCU, and making Moringa leaf soap which contains antioxidants